New Industrial Spaces in Old Industrial Centres: Selected Examples of Sosnowiec (Poland) and České Budějovice (Czech Republic) - Popjaková, Dagmar; Tkocz, Maria; Vančura, Michal (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2014)
As industrial centres, the Polish city of Sosnowiec and the Czech city of České Budějovice developed differently. Sosnowiec was a part of the Upper-Silesian coal region, one of the most important old industrial regions on the European scale. However, until the 1980s, the city had developed not only as a centre of coal extraction and iron metallurgy, but unlike other Upper-Silesian industrial cities, also as a centre with diversified sectoral structure of industry. On the other hand, České Budějovice evolved as a peripheral centre in the southern part of the Czech Republic, i.e. in the region located outside the main industrialized spaces in the country. České Budějovice and the surroundings did not possess, apart from graphites and water, sufficient reserves of minerals. For this reason, since the beginning of industrial development it has been the light (consumer) industry that has played the major role, and in particular the production of beer and stationery. Industrial development of the cities has also differed during the last 20 years. In Sosnowiec, an important part in the regeneration of old industrial areas has been played by the city and European funds. At the same time, all the main old industrial areas maintained their production functions. In České Budějovice on the other hand, it has been the German and Austrian capital. Several industrial areas have altered their former production function into non-production functions.